APLIKASI MANAJEMEN KEUANGAN PRIBADI BERBASIS MOBILE MENGGUNAKAN FRAMEWORK FLUTTER - Teuku Fadjar Shadek; Darpi Darpi; Sawitri Nurhayati; Ilhammullah Ilhammullah (Journal of Innovative and Creativity, 2026)
Personal financial management is a vital aspect of daily life, yet many individuals struggle to record income, expenses, and fund allocations in a structured manner. This study presents the development of a mobile-based personal finance application using the Flutter framework and SQLite database. The application includes features such as income and expense tracking, transaction categorization, monthly and annual summaries, and PDF export. The system was developed using the Waterfall methodology and tested using black-box testing involving several users. The results show that the application functions as intended and supports offline usage, ensuring user data privacy. This solution provides a lightweight, user-friendly tool for personal financial management and serves as a foundation for future feature enhancements.